Rozsirená klasifikace diabetické retinopatie u dĕti a mladistvých - Filous, A; Rychnová, J; Vavrinec, J (Ceskoslovenska pediatrie, 1992)
The authors submit their own modification of the classification of diabetic retinopathy elaborated on the background of several years experience with the examination of children and adolescents with insulin dependent diabetes. The extended classification pattern makes it possible to differentiate and classify more accurately even slight incipient changes detected by chromatooophthalmoscopy. The presence of microaneurysms reflects well the degree of retinal damage in early stages. Special attention must be paid to intraretinal microvascular abnormalities (IRMA). The classification pattern is presented in a table included in the text.
Keywords: Humans; Diabetic Retinopathy; diabetická retinopatie; Adolescent; dítě; lidé; mladiství; Child